Satanism and Anti-Christianity in Black Metal (Semiotics on a Live Concert Video of Black Metal Band Gorgoroth, in Black Mass Event at Krakow, Poland 2004) - Setiawan, Muhammad Ferri; , Rinasari Kusuma, M.I.Kom; , Fajar Junaedi, S.Sos.,M.Si (2014)
Black Metal is a quite popular music genre among teenagers. They like the music as well as the style that the band brings. However, most of them do not aware what the attributes that the band wears convey. Based on that phenomenon, this study focuses on the semantic meaning that is contented in the Black Metal attributes. Specifically, this study analyzes the Satanism and Anti-Christianity symbols in a Black Metal video that is performed by Gorgogoth. Applying a qualitative descriptive method, the symbols found in the video are then analyzed using semiotic theories. The results show that there are 5 symbols belong to Satanism and 3 symbols are identical to Anti-Christianity. Based on the findings, symbols are created intentionally to deliver certain messages and they are used to declare war against Christianity by the Scandinavian Black metal musicians.